Analisis Volatilitas Return Rupiah Terhadap US Dollar dengan Menggunakan GARCH, GJR dan EGARCH - Murharsito . (STIE Pelita Nusantara Semarang, 2014)
This paper attempts to analyze return of Rupiah’s exchange rate to US Dollar. Data is taken from Rupiah/US Dollar exchange rate return form period 2003 to 2013. Analyses are conducted in two ways, first analyzing events that could caused volatility shocks in the observation period. Second, analyzing quantitatively with some models which fit to calculate volatility, they are GARCH, GJR and EGARCH. The result of GARCH analysis concludes that return of Rupiah/US Dollar exchange rate is affected by current exchange rates. Further, those returns also depend on the last period returns. On the other hand, shocks in the volatility of Rupiah/US Dollar persistently occurred. Then, from the analysis uses GJR and EGARCH concluded that positive shocks have greater effect to the conditional return of Rupiah to US Dollar than negative shocks in the future. The strengthen of US Dollar or the weaken of Rupiah will cause greater volatility in the future than the weaken of Rupiah or the strengthen of Dollar in the equivalent level.